Aqua Kit: A Kit for Efficient Freshwater Fish Farming – A Comprehensive Sensor-Based Approach - Chowdhury, Sumit Singha; Roy, Ratnakirti (Leading the Charge: A Guide to Management, Entrepreneurship and Technology in the Dynamic Business Landscape Edition 1, 2025)
Fish farming and aquaculture have been practiced for hundreds of years, and Asia’s country has shared approximately 55% of global production. In recent years, the authorization body has noticed a significant drop in fish farming in fresh water, like ponds, and lakes, and also several unclarities among people on how to take care of fish in artificial aquatic resources. The main causes of that include inadequate optimization a poor understanding of and culture surrounding fisheries a weak approach to fishing a shortage of personnel and a dearth of reliable databases pertaining to aquatic and fisheries resources, weak approach to fisheries, inadequate manpower, water pollution, poor optimization, and not adequate good fisheries knowledge and culture. The integration of Internet of Things (IoT) technology has revolutionized the realm of freshwater fish farming by providing a sophisticated and real-time monitoring system. This paper proposes an innovative approach to enhancing the aquaculture industry through the utilization of various sensors and IoT devices. By continuously monitoring water quality parameters and the well-being of aquatic life, this approach aims to optimize the farming process, mitigate risks, and ensure a sustainable environment for freshwater fish. The proposed solution may cover all of the above aspects to build a healthy fisheries culture and easily connect aqua research and development to continue monitoring to the ground level, it will also help to maintain a proper database to build better aquaculture, maintain the sustainability of nature and aquaculture. The system will be a smart machine learning (deep learning) and Internet of Things (IoT) based system that can detect oxygen, temperature, Ph level, ammonia, water overflow, fish disease, and many more and store the data as (big data) also manage to have user-friendly communication with as well as higher authorities.